Sources of Health Care Among Under-5 Malawian Children With Diarrhea Episodes: An Analysis of the 2017 Demographic and Health Survey - Peter Suwirakwenda Nyasulu PhD; Emery Ngamasana MSc; Ngianga-Bakwin Kandala PhD (SAGE Publishing, 2019)
Diarrhea is a leading cause of morbidity and mortality in the world but mostly in Sub-Saharan Africa. These could be prevented if universal coverage of current available interventions were implemented. The study aimed to identify factors associated with the choice of health care source among caretakers seeking treatment for under-5 children with diarrhea illness. Using women's questionnaire we extracted a subset of data of children aged 0 to 59 months from the 2017 Demographic & Health Survey. Questions regarding history of childhood diarrhea for the past 24 hours or last 2 weeks prior to the survey were key in data extraction. Caregivers were asked to report the place where they sought treatment. In this study, 4 types of health facilities were defined: public, private, pharmacies, and other unspecified sources. A multinomial logistic regression model was used to identify sources of health facility used and corresponding factors associated with the choice. Factors associated with choice of health care source included education (educated women were less likely to self-medicate their children [relative risk ration (RRR) = 0.46; 95% confidence interval (CI) = 0.22-0.94]), income (better income earning families were more likely to seek care from private facility such as pharmacy [RRR = 1.87; 95% CI = 1.14-3.09]), and rural living (those in rural areas were more likely to seek treatment from other unspecified sources [RRR = 7.33, 95% CI = 1.40-38.36]). Public health facilities (79.9%) were the main source of health care service; however, reducing under-5 mortality due to diarrhea illness would require significant efforts to address other inequalities in accessing and utilizing health care services.